High-stakes Entrance Examinations: A View from Brazil - Schwartzman, Simon; Knobel, Marcelo (International Higher Education, 2016)
In Brazil, the growing dominance of the national exam for secondary education as a massive, unified entrance exam for higher education has several detrimental consequences. Besides effectively shaping the high school curriculum, with clear disadvantages for those who will not attend college, it restricts the diversity and regional characteristics of the higher education sector. Similar criticisms apply to other countries that use national entrance exams. Some suggestions for possible changes are given.